Intravitreal Administration Effect of Adipose-Derived Mesenchymal Stromal Cells Combined with Anti-VEGF Nanocarriers, in a Pharmaceutically Induced Animal Model of Retinal Vein Occlusion - Eleni Gounari; Anastasia Komnenou; Evangelia Kofidou; Stavroula Nanaki; Dimitrios Bikiaris; Stavroula Almpanidou; Kokkona Kouzi; Vasileios Karampatakis; George Koliakos (Hindawi Limited, 2022)
Antiangiogenic therapeutic agents (anti-VEGF) have contributed to the treatment of retinal vein occlusion (RVO) while mesenchymal stromal cell- (MSCs-) mediated therapies limit eye degeneration. The aim of the present study is to determine the effect of adipose-derived MSCs (ASCs) combination with nanocarriers of anti-VEGF in a pharmaceutically induced animal model of RVO. Nanoparticles (NPs) of thiolated chitosan (ThioCHI) with encapsulated anti-VEGF antibody were prepared. ASCs were isolated and genetically modified to secrete the green fluorescence GFP. Twenty-four New Zealand rabbits were divided into the I-IV equal following groups: ASCs, ASCs + nanoThioCHI-anti-VEGF, RVO, and control. For the RVO induction, groups I-III received intravitreal (iv) injections of MEK kinase inhibitor, PD0325901. Twelve days later, therapeutic regiments were administered at groups I-II while groups III-IV received BSS. Two weeks later, the retinal damage evaluated via detailed ophthalmic examinations, histological analysis of fixed retinal sections, ELISA for secreted cytokines in peripheral blood or vitreous fluid, and Q-PCR for the expression of related to the occlusion and inflammatory genes. Mild retinal edema and hemorrhages, limited retinal detachment, and vasculature attenuation were observed in groups I and II compared with the pathological symptoms of group III which presented a totally disorganized retinal structure, following of positive immunostaining for neovascularization and related to RVO markers. Important reduction of the high secreted levels of inflammatory cytokines was quantified in groups I and II vitreous fluid, while the expression of the RVO-related and inflammatory genes has been significantly decreased especially in group II. GFP+ ASCs, capable of being differentiated towards neural progenitors, detected in dissociated retina tissues of group II presenting their attachment to damaged area. Conclusively, a stem cell-based therapy for RVO is proposed, accompanied by sustained release of anti-VEGF, in order to combine the paracrine action of ASCs and the progressive reduction of neovascularization.